2012
DOI: 10.1089/ars.2011.4196
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite and Nitrite Reductases: From Molecular Mechanisms to Significance in Human Health and Disease

Abstract: Nitrite, previously considered physiologically irrelevant and a simple end product of endogenous nitric oxide (NO) metabolism, is now envisaged as a reservoir of NO to be activated in response to oxygen (O(2)) depletion. In the first part of this review, we summarize and compare the mechanisms of nitrite-dependent production of NO in selected bacteria and in eukaryotes. Bacterial nitrite reductases, which are copper or heme-containing enzymes, play an important role in the adaptation of pathogens to O(2) limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 364 publications
2
46
0
Order By: Relevance
“…It has been shown that the biological functions of inorganic nitrate and nitrite are mediated, at least in part, by the formation of NO [9,10,13]. Our data shows that the effect of nitrite in reducing O 2 •-production in LPS activated macrophages is mimicked by the NO donor DETA-NONOate, and could be abolished by cPTIO but not by L-NAME.…”
Section: Nitrite Reduces Superoxide Levels In Lps Activated Human Monsupporting
confidence: 45%
See 1 more Smart Citation
“…It has been shown that the biological functions of inorganic nitrate and nitrite are mediated, at least in part, by the formation of NO [9,10,13]. Our data shows that the effect of nitrite in reducing O 2 •-production in LPS activated macrophages is mimicked by the NO donor DETA-NONOate, and could be abolished by cPTIO but not by L-NAME.…”
Section: Nitrite Reduces Superoxide Levels In Lps Activated Human Monsupporting
confidence: 45%
“…Increased production of ROS is considered a major contributing factor to the development and progression of various diseases, including kidney diseases, type 2 diabetes, cardiovascular diseases and neurodegenerative diseases [3][4][5][6]. where these anions may undergo bioconversion to form NO and other bioactive nitrogen oxides [8][9][10]. Nitrate is converted to nitrite by oral bacteria, and subsequent reduction of nitrite to NO can be achieved by a variety of proteins and enzymes in blood and tissues, including xanthine oxidase (XO) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several enzymes and proteins have been implicated in nitrite reduction in the vasculature, including heme proteins such as hemoglobin and myoglobin, enzymes of the respiratory chain, aldehyde oxidase, and XO. 15,37 Our findings emphasize XO as a major nitrite reducer in the renal microvasculature, because XO was highly expressed and inhibitors of the enzyme completely inhibited the nitrite response. The generated NO operates partly by stimulating a NO-soluble guanylyl cyclase-cGMP pathway, but more importantly by inhibiting vascular NADPH oxidase-dependent superoxide signaling.…”
Section: Discussionmentioning
confidence: 61%
“…1) is cytochrome cd 1 nitrite reductase (hereinafter NIR), a homodimer containing one c-heme and one d 1 -heme group in each subunit (58), belonging to the NirS family of nitrite reductases (59). The d 1 -heme is a partially saturated macrocycle, unique to this enzyme and synthesized by a specialized pathway present only in denitrifiers (strongly induced in P. aeruginosa upon nitrite treatment): this specialized cofactor is required for the efficient release of NO (60).…”
Section: Endogenous Sources Of No In P Aeruginosa and Their Effects mentioning
confidence: 99%